Brazil the troubled rise of a global power - Reid, Michael (Yale University Press, 2014)
After decades of military rule, the fourth most populous democracy enjoyed effective reformist leadership that tamed inflation, opened the country up to trade, and addressed poverty and other social issues, enabling Brazil to become more of an essential participant in global affairs. But as it prepares to host the 2014 soccer World Cup and 2016 Olympics, Brazil has been rocked by mass protest. This insightful volume considers the nation's still abundant problems-an inefficient state, widespread corruption, dysfunctional politics, and violent crime in its cities-alongside its achievements to provide a fully rounded portrait of a vibrant country about to take a commanding position on the world stage